Jules Michelet writing art and history in nineteenth-century France - Hannoosh, Michèle 1954- (The Pennsylvania State University Press, 2019)
"Demonstrates the crucial role that art-writing played as a tool of historical analysis in the work of the Romantic historian Jules Michelet's work, decisively influencing his most important historical concepts, his idea of history, and his view of the practice of the historian"--
Keywords: Michelet, Jules -- 1798-1874; Geschichte 1800-1900; Geschichtsschreibung; Kunst; Europa; Frankreich; Michelet, Jules / 1798-1874; Art and history / France / History / 19th century; Historiography / France / History / 19th century; Art and history; Historiography; France; 1800-1899; History